Distributed optimal scheduling for virtual power plant with high penetration of renewable energy - Li, Jing; Mo, Huihong; Sun, Qiming; Wei, Wei; Yin, Kai (International journal of electrical power & energy systems, 2024)
•A scenario clustering and reduction strategy based on the nodal voltage fluctuation is proposed to obtain the input stochastic parameters of the optimization model.•Considering multiple scenarios of renewable energy generation power, a large-scale stochastic optimization model is developed for optimal scheduling of the virtual power plant.•Based on multi-temporal power flow decoupling, a distributed optimization algorithm is proposed to solve the optimization problem in rolling time domain. The virtual power plants are aggregations of distributed generators, grid-connected devices in user side. The operation of virtual power plants affects the economic benefits and environmental benefits. However, due to the stochastic and fluctuating nature of power generation from renewable energy sources, the optimal scheduling problem for the virtual power plant containing high-dimensional random variables is difficult to solve. The conic power flow constraints are considered in the virtual power plant day-ahead optimal scheduling models to maximize the revenue by virtue of optimizing the flexible resources such as energy storage system and interruptible load. To quantify the uncertainties in the optimization problem, this paper proposes a network state-based power scenario reduction strategy for renewable energy generation, where typical scenarios are selected by the state of the grid voltage. The proposed day-ahead scheduling model is a mixed-integer, nonlinear, large-scale, stochastic optimization problem with high dimensional random variables, which is difficult to be solved directly by traditional centralized method. By temporally decoupling the charging and discharging model of energy storage systems, a distributed optimization algorithm is proposed based on multi-temporal power flow decoupling optimization model. The simulation results show that the proposed distributed optimization algorithm has high accuracy and good convergence, the virtual power plant can achieve day-ahead optimal scheduling and effectively promote renewable energy accommodation under the security and reliability of the grid.